A new species of Dascillus Latreille (Coleoptera: Dascillidae) from Hubei, China - Fu, Yuting; Jin, Zhenyu; Wu, Gang (Zootaxa, 2023)
A new species, Dascillus emarginatus sp. nov., from Shennongjia Nature Reserve, Hubei, China is described. The new species is very similar to D. attenuatus Jin, Xie & Zhu, 2017, from which it can be distinguished by the greater body length, scutellar shield emarginate anteriorly, abdominal ventrites with glabrous spots on each side in both genders, apex of female ventrite 5 emarginate in the middle, and the shape of genitalia. The illustrations of the morphological characters and a distribution map are given.